An Improved Coupled Modeling Method for Coalbed Methane Extraction after Hydraulic Fracturing - Hao-Hao Zhang; Jun-Xing Wang; Chao-Jun Fan; Hui-Jie Bi; Li Chen; Chen-Yu Xu (Geofluids)
This paper proposes an improved coupled modeling method for coalbed methane extraction after hydraulic fracturing. Based on the damage mechanics theory, we introduce a state damage variable to record the damage changes at different times and construct the coupling governing equations of the seepage field and solid mechanics field in the hydraulic fracturing process. Then, the results of hydraulic fracturing simulation are used as initial values to perform coupling modeling for coalbed methane extraction. The method is implemented by the combination of different modules in COMSOL to solve the state damage variable, displacement, and pressure. Additionally, two 2D numerical examples are used to verify the precision of this method, and a 3D coalbed methane extraction simulation is performed to analyze the extraction effects and the evolution characteristics of the permeability before and after hydraulic fracturing. Numerical examples show that the proposed coupling modeling method can not only simplify the calculation steps of the CwM method and reduce the numerical errors caused, but also characterize the damage, porosity, permeability, and extraction effect caused by hydraulic fracturing in coal seams with permeability anisotropy.